Aluminium foil as a potential substrate for ATR-FTIR, transflection FTIR or Raman spectrochemical analysis of biological specimens. Issue 3 (11th November 2015) - Cui, Li; Butler, Holly J.; Martin-Hirsch, Pierre L.; Martin, Francis L.
Abstract : Aluminium foil is a potential low-cost alternative substrate for spectrochemical analyses: facilitating translation to a routine clinical or laboratory setting. Abstract : The substantial cost of substrates is an enormous obstacle in the successful translation of biospectroscopy (IR or Raman) into routine clinical/laboratory practice (screening or diagnosis). As a cheap and versatile substrate, we compared the performance of readily available aluminium (Al) foil with low-E, Au-coated and glass slides for cytological and histological specimen analysis by attenuated total reflection Fourier-transform infrared (ATR-FTIR), transflection FTIR or Raman spectroscopy. The low and almost featureless background signal of Al foil enables the acquisition of IR or Raman spectra without substrate interference or sacrificing important fingerprint biochemical information of the specimen, even for very thin samples with thicknesses down to 2 μm. Al foil is shown to perform as well as, if not better than, low-E or Au-coated slide, irrespective of its relatively rough surface. Although transmission FTIR is not possible on Al foil, this work demonstrates Al foil is an inexpensive, readily available and versatile substrate suitable for ATR-FTIR, transflection FTIR or Raman spectrochemical measurements of diverse biological specimens. The features of Al foil demonstrated here could promote a transition towards accessible substrates that can be readily implemented in either research or clinical settings.